THE PHONOLOGICAL ANALYSIS OF A JAPANESE SINGER: THE CRITICISM OF USING SONGS IN ENGLISH TEACHING - Sanjaya, Agung (Sanata Dharma University, 2018)
This study deals with the phonological analysis of a Japanese singer in some English sounds in live performance music videos. It aims to analyse and describe the pronunciation process of Japanese singer in producing tense vowels, diphthongs, and liquids. It also criticizes the use of songs in English teaching based on the findings. The data are from live performance videos of Japanese singer. The researcher watched and listened to the videos. After that, the researcher listed the words in the lyrics of the songs containing tense vowels, diphthongs, and liquids. The words were transcribed into standard phonetic transcription. Then, the researcher transcribed the words into the phonetic transcription according to the pronunciation of the singer. After that, the data were classified into three parts which were the words containing tense vowels, diphthongs, and liquids. After the researcher analyzed the videos, the findings of this study showed that the Japanese singer as an EFL speaker had different pronunciation process in producing tense vowels, diphthongs, and liquids sound. The findings also gave the criticism on the use of songs in English teaching in a form of caution and contribution.DOI: https://doi.org/10.24071/ijhs.2018.020108